THE RIGHT TO THE CITY AND DATA PROTECTION: COMPLEMENTARY FOR DEVELOPING CITIZEN-CENTRIC DIGITAL CITIES? - Breuer, Jonas; Pierson, Jo (AoIR Selected Papers of Internet Research, 2020)
In digital cities, urban space integrates physical and digital worlds. Information and communication technologies, often controlled by private companies, become ubiquitous, not least to capture and process (personal) data. While private governance can reconfigure public values and relations between public institutions and citizens, the question arises who decides what cities become, whose interests they serve. This paper presents ongoing research about the Right to the City (Lefebvre, 1968) and the right to personal data protection, guided by a social constructivist perspective and the methodological framework of actor-network-theory. As part of a four-year research track, we conducted an empirical cross-case analysis of urban data processing projects affected by the GDPR. The aim was to answer the question of how ‘users’ of cities can be represented meaningfully in processes that shape cities by means of those two rights. To do so, we interviewed people directly involved in Belgian ‘smart’ city projects. The main results of this research show that the two rights can be complementary in fostering agency and protecting citizen interests in technologically enhanced, citizen-centric cities. Data protection impacts smart city developments, but true agency of citizens as in the Right to the City remains limited. We will discuss why especially interdisciplinary research is required to further understanding in this complex, cross-domain environment and to lower barriers to citizen inclusion in practice.